Phenotypic and functional immune cell profiling of patients with primary immunodeficiency associated with mycobacterial infections in a tuberculosis endemic region - Van Coller, Ansia (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.